ANTIDIARRHEAL POTENTIALS OF SCHWENCKIA AMERICANA L. (SOLANACEAE): A COMPARATIVE STUDY OF THE AERIAL PART AND ROOT EXTRACTS - A., Nwabunike I.; O., Okoli C.; P., Ezeugwu; C., Ezike A.; A., Onyeto C.; N., Mbaoji F.; O., Ndu O.; M., Onwuka A. (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: Schwenckia americana L. (Solanaceae) is employed as a decoction of either the leaves, roots or the whole plant in the treatment of diarrhoea in most West African countries. Using a comparative study approach, the antidiarrheal potentials of its aerial part and root extracts were evaluated to substantiate its local use in diarrhoea management. Methods: In vivo effects of the extracts on rodent models of diarrhea, enteropooling and gastric motility induced by castor oil were investigated as well as their effects on acetylcholine and histamine-induced guinea pig ileal contractions in vitro. Phytochemical analyses of both extracts were also carried out for tentative identification of constituents and quantitative estimation of total saponin and phenolic contents using standard methods. Results: S. americana L. gave a significant (P<0.001) reduction in the number of fecal droppings and fecal watery texture over 4 h. Gastrointestinal motility and the volume of intestinal content were also significantly (P<0.001) reduced. In vitro studies revealed potent inhibition of guinea pig ileal contractions induced by acetylcholine and histamine by the extracts. However, the anti-diarrheal potentials in the root extract were higher than the aerial part extract, with the root extract exhibiting complete blockade of acetylcholine and histamine-induced ileal contractions and up to 100% inhibition of diarrheic feces passage at 400 mg/kg. The phytochemical analysis also revealed a higher relative abundance of phenols and saponins in the root extract. Conclusion: This research has therefore pioneered the establishment of a scientific proof for the acclaimed anti-diarrheal potentials and hence the ethnomedicinal use of this herb. The existence of higher anti-diarrheal potentials in the root has also been established which could possibly be linked to a higher relative abundance of phenols and saponins in this part.Â